THE ROLE OF SPIRITUAL AND MORAL VALUES IN PERSONAL DEVELOPMENT IN THE HERITAGE OF KHOJA AHMAD YASSAVI - Kenjayeva Dilrabo Rominovna (Bright Mind Publishing, 2026)
This article analyzes the significance of the spiritual and moral views in the heritage of Khoja Ahmad Yassavi in shaping personal development. The scholar’s Sufi teachings, particularly the moral virtues advanced in the work such as purity, honesty, contentment, patience, humility, kindness, and compassion—are examined in terms of their educational essence. Yassavi’s doctrine is interpreted as a spiritual system that serves to cultivate a well-rounded individual through the purification of a person’s inner world.
Keywords: Spirituality, education, upbringing, well-rounded personality, justice, humanism, honesty, moral virtue, behavior, enlightenment.